2019
DOI: 10.1002/mma.5527
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Aedes aegypti populations by limited Wolbachia‐based strategies in a seasonal environment

Abstract: In this work, the linear feedback limited control strategy is proposed to indicate how the Wolbachia‐infected mosquitoes should be introduced in the seasonal environment to reduce the non‐Wolbachia mosquito population. The numerical simulations show that the proposed strategy reduces the population level of non‐Wolbachia mosquitos, avoiding mosquito spread and, consequently, reducing the number of cases of vector‐borne diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In general, stability is an important requirement to study dynamical systems [31][32][33]. In following theorem, we derived the sufficient for exponential stability results for system (25).…”
Section: Stability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In general, stability is an important requirement to study dynamical systems [31][32][33]. In following theorem, we derived the sufficient for exponential stability results for system (25).…”
Section: Stability Analysismentioning
confidence: 99%
“…e integer-order mathematical model which describes the interplay among the wild and Wolbachia-infected mosquitoes was analyzed in [25]. In that work, the author divided the mosquito population into two groups: one is aquatic and another one is adult.…”
Section: Introductionmentioning
confidence: 99%
“…In (Campo-Duarte et al., 2018), the focus is to wipeout WU mosquitoes and Rafikov et al. (Rafikov et al., 2019) strategy is to have more WI mosquitoes than WU mosquitoes. Our modelling work has shown that the focus could be different depending on the dynamics of the Wolbachia strain in the Ae.…”
Section: Optimal Wolbachia Release Problemmentioning
confidence: 99%
“…Different mathematical models have been developed to simulate the introduction of Wolbachia into Ae. aegypti populations (Campo-Duarte, Vasilieva, Cardona-Salgado, & Svinin, 2018; Crain et al., 2011; Ndii, Hickson, & Mercer, 2012; Rafikov, Meza, Correa, & Wyse, 2019; Schraiber et al., 2012; Xue, Manore, Thongsripong, & Hyman, 2017; Zheng, Tang, Yu, & Qiu, 2018), with each specifying conditions that enable WI mosquitoes to dominate. Caspari and Watson (Caspari & Watson, 1959) demonstrated the importance of cytoplasmic incompatibility on the population replacement between WU and WI mosquitoes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation